(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2022)
Vaccine, a cost-effective medicine saves lives. Vaccination during childhood has been implemented worldwide through the expanded program of immunization (EPI) since 1974. It has saved million lives till 2019 globally. South Asian countries have equally benefitted from the EPI executing this strategy through their national immunization programs. The life-course immunization concept aims to extend the vaccination from birth to elderly; some counties have already started focusing on it. Adult vaccination is the process of vaccinating to peoples of 19 years and above. Most of the developed countries have their national policy guidelines on adult immunization but no such national policy for adult vaccination exists in most of the developing and underdeveloped countries including countries of South Asia. South Asian countries have to accept the concept Life-Course Immunization and develop National Adult Immunization Guidelines and vaccinate adults from vaccine preventable diseases highly prevalent in their countries. This could improve quality of human health at all stages of life.